Preliminary field evaluation of black soldier fly frass as an organic fertilizer on maize (Zea mays L.) growth and yield in southeastern Madagascar - Solofondranohatra, Cédrique L.; Ony, Clarcky Andrianorosoa; Burza, Sakib; Fisher, Brian L. (Frontiers in Sustainable Food Systems, 2025)
Food insecurity remains a critical challenge for many farming communities in Madagascar, underscoring the need for sustainable strategies to improve crop yields. Black soldier fly frass (BSFF) is an emerging organic fertilizer, and composting may enhance its agronomic effectiveness. This study evaluated the effects of composted BSFF (CBSFF), fresh BSFF (FBSFF), cattle manure (CM), and a no-fertilizer control on maize (Zea mays L.) germination, height growth, grain yield, and agronomic efficiency of nitrogen (AEN) in southeastern Madagascar’s acidic sandy clay soils. Fertilizers were applied at 43 kg N/ha, reflecting actual farmer practices in the region. This rate represents one-third of the recommendation by FOFIFA (Madagascar’s national agricultural research institute). Farmers in this region rarely apply the full recommended dose due to limited access, high input costs, and low return on investment, factors that contribute to persistent yield gaps even where recommended rates are followed. Maize treated with FBSFF had significantly lower germination rate than all other treatments. In contrast, there were no statistically significant differences in final plant height or grain yield among CBSFF and CM. However, CBSFF-treated plants were on average 6 and 13% taller than those receiving CM and FBSFF, respectively, and produced 38% more grain than CM. All fertilizer treatments yielded significantly more grain than the unfertilized control, which produced no harvestable maize. CBSFF also showed the highest agronomic efficiency of nitrogen (AEN: 46 kg grain/kg N), although this difference was not statistically significant. These results suggest that BSFF, particularly in composted form, can supply sufficient nitrogen to support maize growth. Overall trends point to composted BSFF as the most agronomically effective option. Timing of application should depend on the frass form: composted BSFF is better suited for pre-planting use, while fresh BSFF may be more appropriate after germination. Even at sub-recommended doses, BSFF has the potential to enhance maize productivity and contribute to local food security. Further research across diverse agroecological zones, including trials comparing BSFF with the full recommended fertilizer dose, and economic analyses incorporating frass cost, labor, and transport are recommended to identify optimal application strategies and support widespread adoption by smallholder farmers.